1988
DOI: 10.1002/j.1939-4640.1988.tb01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Radioautographic Localization of Atrial Natriuretic Factor Receptors in the Rat Testis

Abstract: Recent data have suggested that atrial natriuretic factors (ANFs) can modulate Leydig cell functions. An in vitro radioautographic procedure on slide-mounted frozen testicular sections was used to localize ANF receptors in rat testis. The radioligand was rat [125I]ANF-28. It was demonstrated that ANF specific binding sites were present only in interstitial cells, and that the other testicular compartments were not significantly labeled. These results suggest that ANF could have some physiologic role in testicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Evidence of specific ANP binding in isolated adult rat Leydig cells suggested that these hormones activate specific receptors (8). Further studies, using the 125I-ANP radioreceptor methods, confirmed this hypothesis (9,10). Experimental results on cultured murine and rat Leydig cells demonstrated that ANP increases cyclic GMP levels, inducing a selective activation of particulate guanylate cyclase (6,11,12).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Evidence of specific ANP binding in isolated adult rat Leydig cells suggested that these hormones activate specific receptors (8). Further studies, using the 125I-ANP radioreceptor methods, confirmed this hypothesis (9,10). Experimental results on cultured murine and rat Leydig cells demonstrated that ANP increases cyclic GMP levels, inducing a selective activation of particulate guanylate cyclase (6,11,12).…”
mentioning
confidence: 80%
“…In isolated rat Leydig cells this stimulatory effect is still debated. Although ANP receptors have been identified in rat Leydig cells (8)(9)(10) and in spite of the ability of ANP to stimulate cGMP production in these cells, Mukhopadhyay and co-workers (13) did not observe any effect on testosterone secretion. The absence of steroidogenic response to rAP-II has been justified as due to a low guanylate cyclase activity in these cells (13).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the vasodilatory effects of circulating ANP and BNP are partly mediated by local endothelial CNP secretion (Nazario et al, 1995). As Leydig cells have receptors for ANP and BNP (Pelletier 1988;Khurana & Padney 1993) it is tempting to speculate that Leydig cell CNP secretion could be regulated in the same way as in endothelial cells. Interestingly, all natriuretic peptides are known to inhibit endothelial ET-1 secretion (Inagami et al, 1995).…”
Section: Effects Of Natriuretic Peptides On the Testis 57mentioning
confidence: 99%
“…Pelletier, 1988;Mukhopadhyay et al, 1986), adrenocorticotrophin, but not j3-endorphiq dynorphine or a-melanocyte stimulating hormone (Juniewicz et al 1988;Margioris et al, 1989), histamine (Mayerhofer et al, 1989), P-adrenergic agents (Moger & Anakwe, 1986;Tolszczuk et al, 1988), fibroblast growth factor (Sordoillet et al, 1988). transforming growth factor-j3 , activin (Lin e f al., 1989), corticotrophin-releasing factor (Ulisse et al, 1989), renin/ angiotensin I1 (Naruse et al, 1984;Millan & Aguilera, 1988;in man, Okuyama et al, 1988) and calcitonin (Chausmer et nl.. 1982).…”
Section: Potential P a R A C R I N E Mechanisms F O R R E G U L A T Imentioning
confidence: 99%